2017
DOI: 10.1097/bsd.0000000000000396
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Neurological Recovery After Anterior Decompression With Fusion and Posterior Decompression With Laminoplasty for the Treatment of Multilevel Cervical Spondylotic Myelopathy

Abstract: We recommend a individualized approach when it is difficult to determine an anterior or posterior surgery for multilevel CSM. Rehabilitation training should be carried out as early as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The JOA score plateau was achieved at 1 year in the current study as compared to that at 6 months, as reported by Cheung et al [18] and Acharya et al [22] and at 24 months, as reported by Moussellard et al [19]. To further add to the variability in the recovery rate plateau, Ren et al [20] reported a recovery plateau of 9 months.…”
Section: Discussionsupporting
confidence: 77%
“…The JOA score plateau was achieved at 1 year in the current study as compared to that at 6 months, as reported by Cheung et al [18] and Acharya et al [22] and at 24 months, as reported by Moussellard et al [19]. To further add to the variability in the recovery rate plateau, Ren et al [20] reported a recovery plateau of 9 months.…”
Section: Discussionsupporting
confidence: 77%
“…Many studies have shown that the treatment of CSM, including the anterior and posterior approaches, can improve neurologic outcomes. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Nevertheless, some studies have found that anterior surgery can achieve better neurologic improvement than posterior surgery. 11,12,14,16,21,22 However, there are few comparisons between anterior and posterior procedures for four-level CSM.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, for multilevel CSM, the choice of surgical approach remains controversial. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Posterior surgery includes laminoplasty (LAMP) and posterior laminectomy with fusion (PLF). [24][25][26] Posterior surgery can indirectly relieve spinal cord compression by expanding the volume of the spinal canal, allowing the spinal cord to drift backward.…”
Section: Introductionmentioning
confidence: 99%
“…With cervical anterior decompression and fusion, anterior elements of compression on the spinal cord can be directly decompressed, and the spinal cord can be protected by fusion at the level of spinal cord damage. To date, good improvement in neurological symptoms has been reported (JOA score improvement rate of 49.4%-72.9%) [106][107][108][109][110][111][112] , and it has been widely used as the treatment method for cervical degenerative disease. In the 1950s, Robinson, Smith et al 113) , and Cloward et al 114) reported anterior cervical decompression and fusion (anterior cervical discectomy and fusion; ACDF), which involved extraction of the intervertebral disc and bone grafting by anterior approach.…”
Section: Commentarymentioning
confidence: 99%